Evaluation of changing trend in depression, suicidal ideation, and suicide attempts among adolescents with asthma and identification of associated factors: 11-year national data analysis in 788, 411 participants. (10th November 2020) - Kyung, Yechan; Han, Young Joo; Lee, Ju Suk; Lee, Jun Hwa; Jo, Seon Hui; Kim, Sung Hoon
Abstract: Objectives: We identified associated factors for depression and suicidality in adolescents with asthma. Methods: We obtained data from the annual Korea Youth Risk Behavior Web-based Surveys, completed from 2007 to 2017, as a stratified, multistage, clustered sample. Using self-reported questionnaires, students provided yes-or-no answers to questions addressing doctor-diagnosed asthma and self-experienced depression and suicidality. Associated factors for depression and suicidality were tested by logistic regression models after controlling for potential confounding factors. A total of 788, 411 adolescents completed the survey. Results: The prevalence of asthma was similar every year during the survey with 8.9% overall rate. Among them, the prevalence of depression (45.8–29.9%), suicidal ideation (28.6–15.5%), and suicide attempts (9.3–3.9%) decreased. Participants with asthma perceived themselves as unhealthier and unhappier, had more stress, sleep dissatisfaction, depression, suicidal ideation and suicide attempts than did subjects without asthma. In the multivariate model, perception of stress was most strongly associated with depression (adjusted Odds ratio: 4.78, 95% confidence intervals; 4.17–5.06) and suicide attempts (2.51; 1.67–2.93), whereas, perceived unhappiness was most strongly associated with suicidal ideation (4.81; 3.87–5.46) among adolescents with asthma. Asthma itself was also associated with depression, suicidal ideation and suicide attempts (1.12; 1.09–1.22, 1.18; 1.07–1.24, and 1.15; 1.04–1.19, respectively). Conclusion: Although the prevalence of asthma was similar every year, the prevalence of depression and suicidality among adolescents with asthma decreased. Nevertheless, clinical physicians should pay more attention to screen for depression and suicidality among adolescents with asthma, especially having associated factors.